Du bien-fondé de la participation des citoyens aux marchés de permis d’émissions : efficacité économique et questionnements éthiques - Sylvie Ferrari; Mohamed Mehdi Mekni; Emmanuel Petit; Sébastien Rouillon (VertigO)
The idea of regulating pollutions by means of tradable emission permits on a competitive market was developed for the first time by Dales in 1968. The question of the citizens’ participation on these markets received little attention in the economic literature. However, people are allowed to buy emission permits and can therefore reduce the level of pollution by removing them from the market. From a practical viewpoint, the citizen’s preferences are not taken into account neither in the elaboration nor in the functioning of pollution permits markets. However, such a situation does not comply with both the democratic values and the prevailing economic principles. This article aims to discuss the legitimacy of a participation of the citizens to a pollution permits market by introducing both the economic efficiency and the ethical dimension. As the problem of free riding is fundamental when the citizen participation takes place, we show that it can be partly solved by funding the citizen demand. In addition, it seems that the free riding behaviour is overestimated by theoretical economics as experimental economics applied to the game of the public good shows. In addition, the ethical stakes associated to the opening of the pollution markets permits to the citizens are analyzed. An ethics based on the freedom and the sovereignty of the citizens commands us to authorize the participation of the citizens to these markets. This point is finally discussed towards the cumulative pollutions and towards the intergenerational dimension of the equity.